SDLC Approach and Waterfall Method for Development of E-Archive Application for Financing Customer Documents - Agustama Armanda, Akbar; Wulandari, Andini; Armansyah, Armansyah (Journal of Computer Science and Informatics Engineering, 2023)
In business activities, important documents are assets that need to be preserved because they are a history-forming component for a company. In the banking sector, financing customer documents are among the important documents in question. Therefore, these documents need an appropriate archiving mechanism. Document archiving at Bank Syariah Indonesia KCP Medan Pulo Brayan still applies conventional methods. Archiving in this way, can cause accumulation of archives and the risk of damage for one reason or another. This research aims to develop an e-archiving application for financing customer documents that will help anticipate the weaknesses of the conventional method. This application development uses the System Development Life Cycle approach with the waterfall method. Based on the evaluation that has been carried out with prospective end users of this e-archive application, it is concluded that the system can be used and is relevant to the needs.